CAGE18-5 Cruise report : Remotely-operated vehicle (ROV) investigations of active gas seepage sites in the Barents Sea - Bünz, Stefan; Vadakkepuliyambatta, Sunil; Serov, Pavel; Lepland, Aivo; Himmler, Tobias; Hong, Wei-Li; Lindgren, Matteus; Moser, Manuel; Jansson, Pär; Ferre , Benedicte; Svenning, Mette; Dimitri, Kalenitchenko; et al. (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2022)
Cruise CAGE18-5 was the first research expedition under the helm of UiT The Arctic University of Norway in Tromsø with the new ice-going research vessel R/V Kronprins Håkon. This new vessel provides new opportunities to collect cross-disciplinary data for addressing the objectives of the Norwegian Centre of Excellence for Arctic Gas Hydrate, Environment and Climate, CAGE. CAGE investigates Arctic gas hydrate and methane seepage systems in order to better understand the effects they may have on our oceans, ecosystems and global climate. The new research vessel and its facilities allows CAGE access to a state-of-art remotely-operated vehicle, the ROV Ægir 6000, opening a new domain for experimental work and acquisition of sample material from the seafloor. The overall goal of cruise CAGE18-5 therefore was to utilize the ROV in order to provide guided video imagery and to study active gas seepage systems at the gas-hydrate pingo (GHP) site located in the outer Storfjord Trough, and at Storbanken in the northeastern part of the Barents Sea. The cruise may be known as: CAGE18_5